A kind of aging-resistant overhead cable

By using modified outer sheathing material and combining with specific process processing, the problems of insufficient mechanical properties, high temperature resistance and mouse resistance of EPDM rubber-based cable sheathing material are solved, and the aging resistance of the cable is achieved and Improved flame retardancy.

CN118852798BActive Publication Date: 2025-02-07天津市华夏电缆有限公司

Patent Information

Application Number
CN202411333118.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-07
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The existing EPDM rubber-based cable sheathing materials have poor mechanical properties, insufficient high temperature resistance and flammable, making them difficult to meet the current strict usage requirements for cable sheathing materials, and there is also the problem of insufficient rat resistance.

Method used

Using outer sheathing materials including EPDM rubber, zinc oxide, anti-aging agent, flame retardant filler, silane coupling agent, microcrystalline paraffin, vulcanizing agent and crosslinking additive, through specific kneading and vulcanization processes, the The mechanical properties, high temperature resistance, flame retardancy and rat resistance of the cable.

Benefits of technology

显著提升了电缆的耐老化性、防鼠性、力学性能、耐高温性和阻燃性,延长了电缆的使用寿命,并符合绿色环保要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an aging-resistant overhead cable, relates to the field of cables, and comprises a core, an insulating layer and an outer sheath from the inside out, wherein the outer sheath comprises the following raw materials in parts by weight: 100-110 parts of EPDM rubber, 4-6 parts of zinc oxide, 5-7 parts of antioxidant, 45-55 parts of flame retardant filler, 4-6 parts of silane coupling agent, 4-6 parts of microcrystalline wax, 4.5-5.5 parts of vulcanizing agent and 1.5-2.5 parts of crosslinking aid. The antioxidant comprises a hindered phenol structure, a phosphite structure and a capsaicin structure, and improves the aging resistance and rodent resistance of the overhead cable. The flame retardant filler comprises a POSS structure, a castor oil-based unsaturated alkane long chain and an organic montmorillonite, and improves the mechanical properties, high temperature resistance and flame retardancy of the overhead cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of cables, and in particular to an aging-resistant overhead cable. Background Art

[0002] Overhead cables are overhead wires equipped with an insulating layer and a protective sheath. They are a new high-voltage power transmission method between overhead wires and underground cables. According to the structure, they can be divided into hard aluminum wire structure, hard-drawn copper wire structure, aluminum alloy wire structure, steel core or aluminum alloy core support structure and self-supporting three-core composite structure. They have the main characteristics of high power supply reliability, good power supply safety, convenient installation and maintenance, and reasonable economy. EPDM rubber is a non-polar rubber with a main chain containing chemically stable saturated hydrocarbons and a side chain containing unsaturated hydrocarbons. Due to its excellent insulation, moisture resistance and cold resistance, it is widely used in cable insulation and sheath materials. However, EPDM rubber has poor mechanical properties, insufficient high temperature resistance and is flammable, and is increasingly unable to meet the current stringent requirements for cable sheath materials.

[0003] The safety and stability of cables used in some important places have always attracted people's attention. However, due to environmental reasons, the wires and cables laid in these places and used for important equipment will be bitten and damaged by rats, affecting the normal operation of the cables and even causing large-scale power outages and communication interruptions. Usually, rat repellents are added to the cable sheath materials. After the rats are killed by the rat repellents containing toxic substances, they will not only pollute the environment, but also cause the rats' predators to die by eating the rats, thus causing indirect harm to humans and other animals.

[0004] Therefore, it is necessary to develop a suitable modification method to improve the mechanical properties, flame retardancy, high temperature resistance and rodent resistance of EPDM rubber-based cable sheath materials in order to solve the problems encountered in the current use process. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides an aging-resistant overhead cable.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] An aging-resistant overhead cable comprises a wire core, an insulating layer and an outer sheath from the inside out, wherein the wire core is located in the innermost layer, the insulating layer is coated on the outer periphery of the conductor, and the outer sheath is coated on the outer periphery of the insulating layer; the wire core is formed by twisting a plurality of hard aluminum wires; the insulating layer is made of fluororubber;

[0008] The outer sheath comprises the following raw materials in parts by weight: 100-110 parts of EPDM rubber, 4-6 parts of zinc oxide, 5-7 parts of antioxidant, 45-55 parts of flame retardant filler, 4-6 parts of silane coupling agent, 4-6 parts of microcrystalline wax, 4.5-5.5 parts of vulcanizing agent and 1.5-2.5 parts of crosslinking agent; the silane coupling agent is vinyl tris (2-methoxyethoxy) silane, the vulcanizing agent is diisopropylbenzene peroxide, and the crosslinking agent is triallyl isocyanurate;

[0009] The preparation of the aging-resistant overhead cable comprises the following steps:

[0010] Step S1: placing the EPDM rubber material in an internal mixer, mixing at 120-130°C for 2 minutes, adding zinc oxide, antioxidant, and microcrystalline wax, continuing to mix for 5-10 minutes, adding flame retardant filler and silane coupling agent, continuing to mix for 3-5 minutes, transferring to an open mixer, adding a vulcanizing agent and a cross-linking aid, and thinning for 10 minutes, unrolling, standing for 24 hours, transferring to a vulcanizing agent, vulcanizing at 170°C for 20 minutes, and standing for 24 hours to obtain an outer sheath material;

[0011] Step S2: twisting a number of hard aluminum wires to form a wire core; extruding fluororubber on the outer periphery of the wire core to form an insulating layer; and finally extruding the outer sheath material on the outer periphery of the insulating layer to form an outer sheath, thereby obtaining an aging-resistant overhead cable.

[0012] The preparation of the antioxidant comprises the following steps:

[0013] Step A1: add capsaicin and toluene into a flask, start stirring, then add sodium hydroxide solution, stir for 5-10 minutes, then slowly drop epichlorohydrin into the flask, stir and react at room temperature for 6-7 hours, filter, extract and dry to obtain the epoxy product;

[0014] Further, the usage ratio of capsaicin, toluene, sodium hydroxide solution and epichlorohydrin is 0.1 mol: 85-95 mL: 5-10 mL: 0.1 mol, and the mass fraction of sodium hydroxide solution is 10%;

[0015] During the reaction of step A1, the phenolic hydroxyl group in capsaicin reacts with epichlorohydrin to generate an epoxy product;

[0016] Step A2: In a nitrogen atmosphere, add 3,5-di-tert-butyl-4-hydroxyphenylacetic acid and toluene into a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product into the flask, stir and react for 8-10h, then heat to 110-120°C, stir for 1-2h to obtain an alcohol hydroxyl product;

[0017] Further, the usage ratio of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid, toluene, pyridine and epoxidation product is 0.1 mol: 140-150 mL: 0.010-0.015 mol: 0.1 mol;

[0018] During the reaction of step A2, the carboxyl group of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid reacts with the epoxy group of the epoxy product to form an alcohol hydroxyl product;

[0019] Step A3: Add the alcoholic hydroxyl product to toluene, stir for 5-10 minutes to obtain a toluene solution of the alcoholic hydroxyl product, add diethylphosphite chloride and triethylamine to a flask, slowly drop the toluene solution of the alcoholic hydroxyl product into the flask at 40°C, stir at a constant temperature for 1 hour, heat to 60°C, stir at a constant temperature for 5-6 hours, cool to 30°C, filter, wash the filter cake with toluene, distill under reduced pressure at 70°C, and then distill under vacuum at 80°C until no droplets flow out, to obtain an antioxidant;

[0020] Further, the usage ratio of the alcoholic hydroxyl product and toluene is 0.1 mol: 150-160 mL; the usage ratio of diethylphosphite chloride, triethylamine, and toluene solution of the alcoholic hydroxyl product is 23.4-24.5 g: 20-25 mL: 155-165 mL;

[0021] During the reaction of step A3, diethylphosphite chloride reacts with the hydroxyl group of the alcoholic hydroxyl product to generate an antioxidant containing phosphite.

[0022] The flame retardant filler is prepared by the following steps:

[0023] Step B1: In a nitrogen atmosphere, castor oil was added to a reaction bottle, refluxed and stirred, aminopropyl heptaisobutyl POSS (supplier: Guangzhou Yixin Technology Co., Ltd.) and sodium methoxide were added, and refluxed and stirred at 100-110° C. for 24 h to obtain a hydroxyl product;

[0024] Further, the ratio of castor oil, aminopropyl heptaisobutyl POSS and sodium methoxide is 100-110 g: 60-65 g: 5-6 g;

[0025] During the reaction of step B1, castor oil undergoes an amidation reaction with the amino group of aminopropyl heptaisobutyl POSS to obtain a hydroxyl product;

[0026] Step B2: Add the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide into a flask to obtain a mixed solution 1; add 4-dimethylaminobenzoyl chloride into dimethyl sulfoxide to obtain a mixed solution 2; slowly dropwise add the mixed solution 2 into the mixed solution 1 in an ice-water bath at 0°C; after the dropwise addition is completed, heat to 40°C, stir and react at a constant temperature for 8-10 hours, and distill under reduced pressure to obtain a tertiary amine product;

[0027] Further, the dosage ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 140-150 g: 0.01-0.015 mol: 0.1 mol: 260-270 mL; the dosage ratio of 4-dimethylaminobenzoyl chloride and dimethyl sulfoxide is 0.1 mol: 40-50 mL; the dosage ratio of the mixed solution 1 and the mixed solution 2 is 265-275 mL: 45-55 mL;

[0028] During the reaction of step B2, the hydroxyl group of the hydroxyl product reacts with 4-dimethylaminobenzoyl chloride to generate a tertiary amine product;

[0029] Step B3: placing the tertiary amine product and ethanol in a flask, stirring, then adding 1-chloropentane, heating to 50-60°C, stirring and reacting at a constant temperature for 10-12h, revolving and recrystallizing with acetone, filtering, and obtaining a quaternary ammonium salt; adding distilled water, ethanol, and quaternary ammonium salt to a three-necked flask, heating to 80°C with stirring, then adding montmorillonite, continuing to stir and react for 12-14h, then washing with ethanol, vacuum drying, and grinding to obtain a flame retardant filler;

[0030] Further, the dosage ratio of the tertiary amine product, ethanol, and 1-chloropentane is 155-165 g: 335-345 mL: 0.1 mol, and the volume fraction of ethanol is 95%; the dosage ratio of distilled water, ethanol, quaternary ammonium salt, and montmorillonite is 60 mL: 60 mL: 163-173 g: 10 g;

[0031] During the reaction of step B3, the tertiary amine product reacts with 1-chloropentane to form a quaternary ammonium salt. The positively charged part of the quaternary ammonium salt replaces the inorganic ions such as magnesium and aluminum in the montmorillonite layer, thereby entering the montmorillonite layer, expanding the interlayer distance of the montmorillonite, and making the montmorillonite organic, thereby obtaining a flame retardant filler.

[0032] Beneficial effects of the invention: The invention discloses an aging-resistant overhead cable, which comprises a wire core, an insulating layer and an outer sheath from the inside out. The insulating layer is fluororubber, which has excellent aging resistance and meets the use requirements of aging-resistant overhead cables; the outer sheath comprises the following raw materials: ethylene propylene diene rubber, zinc oxide, an antioxidant, a flame retardant filler, a silane coupling agent, microcrystalline wax, a vulcanizing agent and a cross-linking aid.

[0033] The synthesized antioxidant includes hindered phenol structure, phosphite structure and capsaicin structure in its molecule; the hindered phenol structure generates hydroperoxide in the oxidative degradation reaction of the polymer to terminate the oxidative degradation reaction, while the phosphite can reduce and decompose the hydroperoxide, and the hindered phenol structure and the phosphite structure produce rapid intramolecular synergistic effect to prevent the polymer oxidation reaction from continuing and improve the aging resistance of the outer sheath; capsaicin is a natural plant-based material, which will produce a "burning sensation" and irritation effect in the mouth, nose and throat of animals to prevent mice from continuing to gnaw, and will not have adverse effects on the material matrix, which meets the requirements of green environmental protection and makes the antioxidant have rodent-proof performance; the long chain of alkane containing carbon-carbon double bonds in capsaicin can also increase the cross-linking density of the vulcanization system in the outer sheath material, so that the antioxidant has better dispersion compatibility in the matrix and is not easy to migrate and disperse; adding the synthesized antioxidant can improve the aging resistance and rodent-proofness of the overhead cable and extend the service life of the cable.

[0034] The synthesized flame retardant filler includes a POSS structure, a castor oil-based unsaturated alkane long chain, and an organized montmorillonite in its molecules; the POSS structure has strong thermal stability, improves the high temperature resistance of the flame retardant filler, and enables the sheath layer to still have a stable protective effect at high temperatures; castor oil is a renewable vegetable oil with high yield and is inedible, and is an ideal petroleum-based alternative material that meets environmental protection requirements; the long alkane chain containing carbon-carbon double bonds participates in the crosslinking of the rubber system of the outer sheath material, and is helpful for the dispersion of the flame retardant filler in the matrix; the dispersion compatibility of the organized montmorillonite with the polymer matrix is ​​enhanced, which not only improves the mechanical properties of the sheath layer material, but also can form a stable mica layered structure at high temperature, delays the volatilization of flammable gases and the diffusion of oxygen, and can effectively resist the spread and combustion of flames; the addition of the synthesized flame retardant filler improves the mechanical properties, high temperature resistance, and flame retardancy of the cable. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Embodiment 1: An antioxidant, the preparation of which comprises the following steps:

[0037] Step A1: add capsaicin and toluene into a flask, start stirring, then add sodium hydroxide solution, stir for 5 minutes, then slowly drop epichlorohydrin into the flask, stir and react for 6 hours at room temperature, filter, extract and dry to obtain an epoxy product; the amount ratio of capsaicin, toluene, sodium hydroxide solution and epichlorohydrin is 0.1 mol: 85 mL: 5 mL: 0.1 mol, and the mass fraction of sodium hydroxide solution is 10%;

[0038] Step A2: In a nitrogen atmosphere, 3,5-di-tert-butyl-4-hydroxyphenylacetic acid and toluene are added to a flask, the temperature is raised to 45°C, pyridine is added, stirring is started, the epoxy product is added to the flask, stirring and reacting for 8 hours, then the temperature is raised to 110°C, stirring for 1 hour, and an alcohol hydroxyl product is obtained; the amount ratio of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid, toluene, pyridine and epoxy product is 0.1 mol: 140 mL: 0.010 mol: 0.1 mol;

[0039] Step A3: Add the alcoholic hydroxyl product to toluene, stir for 5 minutes to obtain a toluene solution of the alcoholic hydroxyl product, add diethylphosphite chloride and triethylamine to a flask, slowly drop the toluene solution of the alcoholic hydroxyl product into the flask at 40°C, stir at a constant temperature for 1 hour, heat to 60°C, stir at a constant temperature for 5 hours, cool to 30°C, filter, wash the filter cake with toluene, distill under reduced pressure at 70°C, and then vacuum distill at 80°C until no liquid drops out, to obtain an antioxidant; the amount ratio of the alcoholic hydroxyl product to toluene is 0.1 mol: 150 mL; the amount ratio of diethylphosphite chloride, triethylamine, and the toluene solution of the alcoholic hydroxyl product is 23.4 g: 20 mL: 155 mL.

[0040] Embodiment 2: An antioxidant, the preparation of which comprises the following steps:

[0041] Step A1: add capsaicin and toluene into a flask, start stirring, then add sodium hydroxide solution, stir for 8 minutes, then slowly drop epichlorohydrin into the flask, stir and react at room temperature for 6.5 hours, filter, extract and dry to obtain an epoxy product; the amount ratio of capsaicin, toluene, sodium hydroxide solution and epichlorohydrin is 0.1 mol: 90 mL: 8 mL: 0.1 mol, and the mass fraction of sodium hydroxide solution is 10%;

[0042] Step A2: In a nitrogen atmosphere, 3,5-di-tert-butyl-4-hydroxyphenylacetic acid and toluene are added to a flask, the temperature is raised to 45°C, pyridine is added, stirring is started, the epoxy product is added to the flask, stirring and reacting for 9 hours, then the temperature is raised to 115°C, stirring for 1.5 hours, and an alcohol hydroxyl product is obtained; the amount ratio of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid, toluene, pyridine and epoxy product is 0.1 mol: 145 mL: 0.013 mol: 0.1 mol;

[0043] Step A3: Add the alcoholic hydroxyl product to toluene, stir for 8 minutes to obtain a toluene solution of the alcoholic hydroxyl product, add diethylphosphite chloride and triethylamine to a flask, slowly drop the toluene solution of the alcoholic hydroxyl product into the flask at 40°C, stir at a constant temperature for 1 hour, heat to 60°C, stir at a constant temperature for 5.5 hours, cool to 30°C, filter, wash the filter cake with toluene, distill under reduced pressure at 70°C, and then vacuum distill at 80°C until no droplets flow out, to obtain an antioxidant; the amount ratio of the alcoholic hydroxyl product to toluene is 0.1 mol: 155 mL; the amount ratio of diethylphosphite chloride, triethylamine, and the toluene solution of the alcoholic hydroxyl product is 23.9 g: 23 mL: 160 mL.

[0044] Embodiment 3: An antioxidant, the preparation of which comprises the following steps:

[0045] Step A1: add capsaicin and toluene into a flask, start stirring, then add sodium hydroxide solution, stir for 10 minutes, then slowly drop epichlorohydrin into the flask, stir and react for 7 hours at room temperature, filter, extract and dry to obtain an epoxy product; the amount ratio of capsaicin, toluene, sodium hydroxide solution and epichlorohydrin is 0.1 mol: 95 mL: 10 mL: 0.1 mol, and the mass fraction of sodium hydroxide solution is 10%;

[0046] Step A2: In a nitrogen atmosphere, 3,5-di-tert-butyl-4-hydroxyphenylacetic acid and toluene are added to a flask, the temperature is raised to 45° C., pyridine is added, stirring is started, the epoxy product is added to the flask, stirring and reacting for 10 hours, then the temperature is raised to 120° C., stirring for 2 hours, and an alcohol hydroxyl product is obtained; the amount ratio of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid, toluene, pyridine and epoxy product is 0.1 mol: 150 mL: 0.015 mol: 0.1 mol;

[0047] Step A3: Add the alcoholic hydroxyl product to toluene, stir for 10 minutes to obtain a toluene solution of the alcoholic hydroxyl product, add diethylphosphite chloride and triethylamine to a flask, slowly drop the toluene solution of the alcoholic hydroxyl product into the flask at 40°C, stir at a constant temperature for 1 hour, heat to 60°C, stir at a constant temperature for 6 hours, cool to 30°C, filter, wash the filter cake with toluene, distill under reduced pressure at 70°C, and then distill under vacuum at 80°C until no liquid drops out, thereby obtaining an antioxidant; the amount ratio of the alcoholic hydroxyl product to toluene is 0.1 mol: 160 mL; the amount ratio of diethylphosphite chloride, triethylamine, and the toluene solution of the alcoholic hydroxyl product is 24.5 g: 25 mL: 165 mL.

[0048] Embodiment 4: A flame retardant filler, the preparation of which comprises the following steps:

[0049] Step B1: In a nitrogen atmosphere, castor oil was added to a reaction bottle, refluxed and stirred, aminopropyl heptaisobutyl POSS (supplier: Guangzhou Yixin Technology Co., Ltd.) and sodium methoxide were added, and refluxed and stirred at 100° C. for 24 h to obtain a hydroxyl product; the amount ratio of castor oil, aminopropyl heptaisobutyl POSS and sodium methoxide was 100 g:60 g:5 g;

[0050] Step B2: Add the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide into a flask to obtain a mixed solution 1; add 4-dimethylaminobenzoyl chloride to dimethyl sulfoxide to obtain a mixed solution 2, slowly dropwise add the mixed solution 2 into the mixed solution 1 in a 0°C ice-water bath, after the dropwise addition is completed, heat to 40°C, stir and react at a constant temperature for 8 hours, and distill under reduced pressure to obtain a tertiary amine product; the amount ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 140g:0.01mol:0.1mol:260mL; the amount ratio of 4-dimethylaminobenzoyl chloride and dimethyl sulfoxide is 0.1mol:40mL; the amount ratio of the mixed solution 1 to the mixed solution 2 is 265mL:45mL;

[0051] Step B3: Place the tertiary amine product and ethanol in a flask, start stirring, then add 1-chloropentane, heat to 50°C, stir and react at a constant temperature for 10 hours, recrystallize with acetone after rotary evaporation, and filter to obtain a quaternary ammonium salt; add distilled water, ethanol, and quaternary ammonium salt to a three-necked flask, heat to 80°C with stirring, then add montmorillonite, continue stirring and react for 12 hours, then wash with ethanol, vacuum dry, and grind to obtain a flame retardant filler; the amount ratio of the tertiary amine product, ethanol, and 1-chloropentane is 155g:335mL:0.1mol, and the volume fraction of ethanol is 95%; the amount ratio of distilled water, ethanol, quaternary ammonium salt, and montmorillonite is 60mL:60mL:163g:10g.

[0052] Embodiment 5: A flame retardant filler, the preparation of which comprises the following steps:

[0053] Step B1: In a nitrogen atmosphere, castor oil was added to a reaction bottle, refluxed and stirred, aminopropyl heptaisobutyl POSS (supplier: Guangzhou Yixin Technology Co., Ltd.) and sodium methoxide were added, and refluxed and stirred at 105° C. for 24 h to obtain a hydroxyl product; the amount ratio of castor oil, aminopropyl heptaisobutyl POSS and sodium methoxide was 105 g: 63 g: 5.5 g;

[0054] Step B2: Add the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide into a flask to obtain a mixed solution 1; add 4-dimethylaminobenzoyl chloride to dimethyl sulfoxide to obtain a mixed solution 2, slowly dropwise add the mixed solution 2 into the mixed solution 1 in a 0°C ice-water bath, after the dropwise addition is completed, heat to 40°C, stir and react at a constant temperature for 9 hours, and distill under reduced pressure to obtain a tertiary amine product; the amount ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 145g:0.013mol:0.1mol:265mL; ​​the amount ratio of 4-dimethylaminobenzoyl chloride and dimethyl sulfoxide is 0.1mol:45mL; the amount ratio of the mixed solution 1 to the mixed solution 2 is 270mL:50mL;

[0055] Step B3: Place the tertiary amine product and ethanol in a flask, start stirring, then add 1-chloropentane, heat to 55°C, stir and react at constant temperature for 11 hours, recrystallize with acetone after rotary evaporation, and filter to obtain a quaternary ammonium salt; add distilled water, ethanol, and quaternary ammonium salt to a three-necked flask, heat to 80°C with stirring, then add montmorillonite, continue stirring and react for 13 hours, then wash with ethanol, vacuum dry, and grind to obtain a flame retardant filler; the amount ratio of the tertiary amine product, ethanol, and 1-chloropentane is 160g:340mL:0.1mol, and the volume fraction of ethanol is 95%; the amount ratio of distilled water, ethanol, quaternary ammonium salt, and montmorillonite is 60mL:60mL:168g:10g.

[0056] Embodiment 6: A flame retardant filler, the preparation of which comprises the following steps:

[0057] Step B1: In a nitrogen atmosphere, castor oil was added to a reaction bottle, refluxed and stirred, aminopropyl heptaisobutyl POSS (supplier: Guangzhou Yixin Technology Co., Ltd.) and sodium methoxide were added, and refluxed and stirred at 110° C. for 24 h to obtain a hydroxyl product; the amount ratio of castor oil, aminopropyl heptaisobutyl POSS and sodium methoxide was 110 g: 65 g: 6 g;

[0058] Step B2: Add the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide into a flask to obtain a mixed solution 1; add 4-dimethylaminobenzoyl chloride to dimethyl sulfoxide to obtain a mixed solution 2, slowly dropwise add the mixed solution 2 into the mixed solution 1 in a 0°C ice-water bath, after the dropwise addition is completed, heat to 40°C, stir and react at a constant temperature for 10 hours, and distill under reduced pressure to obtain a tertiary amine product; the amount ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 150g:0.015mol:0.1mol:270mL; the amount ratio of 4-dimethylaminobenzoyl chloride and dimethyl sulfoxide is 0.1mol:50mL; the amount ratio of the mixed solution 1 to the mixed solution 2 is 275mL:55mL;

[0059] Step B3: Place the tertiary amine product and ethanol in a flask, start stirring, then add 1-chloropentane, heat to 60°C, stir and react at constant temperature for 12 hours, recrystallize with acetone after rotary evaporation, and filter to obtain a quaternary ammonium salt; add distilled water, ethanol, and quaternary ammonium salt to a three-necked flask, heat to 80°C with stirring, then add montmorillonite, continue stirring and react for 14 hours, then wash with ethanol, vacuum dry, and grind to obtain a flame retardant filler; the amount ratio of the tertiary amine product, ethanol, and 1-chloropentane is 165g:345mL:0.1mol, and the volume fraction of ethanol is 95%; the amount ratio of distilled water, ethanol, quaternary ammonium salt, and montmorillonite is 60mL:60mL:173g:10g.

[0060] Embodiment 7: An aging-resistant overhead cable, comprising a core, an insulating layer and an outer sheath from the inside out, wherein the core is located in the innermost layer, the insulating layer is coated on the outer periphery of the conductor, and the outer sheath is coated on the outer periphery of the insulating layer; the core is formed by twisting a plurality of hard aluminum wires; the insulating layer is made of fluororubber; the outer sheath comprises the following raw materials in parts by weight: 100 parts of EPDM rubber, 4 parts of zinc oxide, 5 parts of antioxidant, 45 parts of flame retardant filler, 4 parts of silane coupling agent, 4 parts of microcrystalline wax, 4.5 parts of vulcanizing agent and 1.5 parts of crosslinking aid; the silane coupling agent is vinyl tris (2-methoxyethoxy) silane, the vulcanizing agent is diisopropylbenzene peroxide, and the crosslinking aid is triallyl isocyanurate;

[0061] The preparation of the aging-resistant overhead cable comprises the following steps:

[0062] Step S1: placing the EPDM rubber material in an internal mixer, mixing at 120°C for 2 minutes, adding zinc oxide, the antioxidant obtained in Example 1, and microcrystalline wax, and continuing to mix for 5 minutes, adding the flame retardant filler and silane coupling agent obtained in Example 4, and continuing to mix for 3 minutes, transferring to an open mixer, adding a vulcanizing agent and a crosslinking aid, and thinning for 10 minutes, unrolling, standing for 24 hours, transferring to a vulcanizing agent, vulcanizing at 170°C for 20 minutes, and standing for 24 hours, to obtain an outer sheath material;

[0063] Step S2: twist 14 hard aluminum wires to form a wire core; extrude fluororubber on the outer periphery of the wire core to form an insulating layer; finally extrude the outer sheath material on the outer periphery of the insulating layer to form an outer sheath, thereby obtaining an aging-resistant overhead cable.

[0064] Embodiment 8: An aging-resistant overhead cable, comprising a core, an insulating layer and an outer sheath from the inside out, wherein the core is located in the innermost layer, the insulating layer is coated on the outer periphery of the conductor, and the outer sheath is coated on the outer periphery of the insulating layer; the core is formed by twisting a plurality of hard aluminum wires; the insulating layer is made of fluororubber; the outer sheath comprises the following raw materials in parts by weight: 105 parts of EPDM rubber, 5 parts of zinc oxide, 6 parts of antioxidant, 50 parts of flame retardant filler, 5 parts of silane coupling agent, 5 parts of microcrystalline wax, 5.0 parts of vulcanizing agent and 2.0 parts of crosslinking aid; the silane coupling agent is vinyl tris(2-methoxyethoxy) silane, the vulcanizing agent is diisopropylbenzene peroxide, and the crosslinking aid is triallyl isocyanurate;

[0065] The preparation of the aging-resistant overhead cable comprises the following steps:

[0066] Step S1: placing the EPDM rubber material in an internal mixer, mixing at 125°C for 2 minutes, adding zinc oxide, the antioxidant obtained in Example 2, and microcrystalline wax, and continuing to mix for 8 minutes, adding the flame retardant filler and silane coupling agent obtained in Example 5, and continuing to mix for 4 minutes, transferring to an open mixer, adding a vulcanizing agent and a crosslinking aid, and thinning for 10 minutes, unrolling, standing for 24 hours, transferring to a vulcanizing agent, vulcanizing at 170°C for 20 minutes, and standing for 24 hours, to obtain an outer sheath material;

[0067] Step S2: twist 16 hard aluminum wires to form a wire core; extrude fluororubber on the outer periphery of the wire core to form an insulating layer; finally extrude the outer sheath material on the outer periphery of the insulating layer to form an outer sheath, thereby obtaining an aging-resistant overhead cable.

[0068] Embodiment 9: An aging-resistant overhead cable, comprising a core, an insulating layer and an outer sheath from the inside out, wherein the core is located in the innermost layer, the insulating layer is coated on the outer periphery of the conductor, and the outer sheath is coated on the outer periphery of the insulating layer; the core is formed by twisting a plurality of hard aluminum wires; the insulating layer is made of fluororubber; the outer sheath comprises the following raw materials in parts by weight: 110 parts of EPDM rubber, 6 parts of zinc oxide, 7 parts of antioxidant, 55 parts of flame retardant filler, 6 parts of silane coupling agent, 6 parts of microcrystalline wax, 5.5 parts of vulcanizing agent and 2.5 parts of crosslinking aid; the silane coupling agent is vinyl tris (2-methoxyethoxy) silane, the vulcanizing agent is diisopropylbenzene peroxide, and the crosslinking aid is triallyl isocyanurate;

[0069] The preparation of the aging-resistant overhead cable comprises the following steps:

[0070] Step S1: placing the EPDM rubber material in an internal mixer, mixing at 130°C for 2 minutes, adding zinc oxide, the antioxidant obtained in Example 3, and microcrystalline wax, and continuing to mix for 10 minutes, adding the flame retardant filler and silane coupling agent obtained in Example 6, and continuing to mix for 5 minutes, transferring to an open mixer, adding a vulcanizing agent and a crosslinking aid, and thinning for 10 minutes, unrolling, standing for 24 hours, transferring to a vulcanizing agent, vulcanizing at 170°C for 20 minutes, and standing for 24 hours, to obtain an outer sheath material;

[0071] Step S2: twisting 18 hard aluminum wires to form a wire core; extruding fluororubber on the outer periphery of the wire core to form an insulating layer; and finally extruding the outer sheath material on the outer periphery of the insulating layer to form an outer sheath to obtain an aging-resistant overhead cable.

[0072] Comparative Example 1

[0073] Compared with Example 9, the antioxidant is replaced with the alcohol hydroxyl product in Example 3, that is, no phosphite is introduced, and the rest is exactly the same as Example 9 to prepare an aging-resistant overhead cable.

[0074] Comparative Example 2

[0075] Compared with Example 9, the hydroxyl product used in the preparation process of the flame retardant filler obtained in Example 6 was replaced with castor oil, that is, the POSS structure was not introduced, and the rest was exactly the same as in Example 9 to prepare an aging-resistant overhead cable.

[0076] The aging-resistant overhead cable prepared by the present invention is further tested for its effect, and the test results are as follows.

[0077] In order to test the aging-resistant overhead cable prepared by the present invention, the outer sheath materials of the aging-resistant overhead cables obtained in Examples 7-9 and Comparative Examples 1-2 were subjected to tensile strength and elongation at break tests according to the standard method of GB / T2951.11-2008 "General Test Methods for Insulation and Sheath Materials of Electric Cables and Optical Cables"; the outer sheath material was placed at a high temperature of 200°C for 4 hours, and the tensile strength retention rate was measured; the oxygen index was tested according to the standard of GB / T2406.1-2008 "Determination of Combustion Behavior by Oxygen Index Method for Plastics"; the rodent-proof performance was tested according to the standard of GB / T34016-2017; the outer sheath material was placed in an air box and aged at 120°C for 168 hours, and the change rate of tensile strength and elongation at break was tested according to the method of GB / T2951.11-2008, and the results are recorded in Table 1;

[0078] Table 1: Test results

[0079]

[0080] According to the data in Table 1, the aging-resistant overhead cable prepared by the present invention has good aging resistance, rodent resistance, mechanical properties, high temperature resistance and flame retardancy. Comparison between Example 9 and Comparative Example 1 shows that the use of an antioxidant, the introduction of a phosphite structure and hindered phenols synergistically prevents the polymer aging reaction from continuing, and improves the aging resistance of the cable; comparison between Example 9 and Comparative Example 2 shows that the use of a flame-retardant filler and the introduction of a POSS structure are beneficial to the improvement of the high temperature resistance of the cable.

[0081] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. An aging-resistant overhead cable, characterized in that: From the inside to the outside, it includes a core, an insulating layer and an outer sheath, the core is located in the innermost layer, the insulating layer is coated on the outer periphery of the conductor, and the outer sheath is coated on the outer periphery of the insulating layer; the outer sheath includes the following raw materials in parts by weight: 100-110 parts of EPDM rubber, 4-6 parts of zinc oxide, 5-7 parts of antioxidant, 45-55 parts of flame retardant filler, 4-6 parts of silane coupling agent, 4-6 parts of microcrystalline wax, 4.5-5.5 parts of vulcanizing agent and 1.5-2.5 parts of cross-linking aid; The preparation of the antioxidant comprises the following steps: Step A1: add capsaicin and toluene into a flask, start stirring, then add sodium hydroxide solution, stir for 5-10 minutes, then slowly drop epichlorohydrin into the flask, stir and react at room temperature for 6-7 hours, filter, extract and dry to obtain the epoxy product; Step A2: In a nitrogen atmosphere, add 3,5-di-tert-butyl-4-hydroxyphenylacetic acid and toluene into a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product into the flask, stir and react for 8-10h, then heat to 110-120°C, stir for 1-2h to obtain an alcohol hydroxyl product; Step A3: Add the alcoholic hydroxyl product to toluene, stir for 5-10 minutes to obtain a toluene solution of the alcoholic hydroxyl product, add diethylphosphite chloride and triethylamine to a flask, slowly drop the toluene solution of the alcoholic hydroxyl product into the flask at 40°C, stir at a constant temperature for 1 hour, heat to 60°C, stir at a constant temperature for 5-6 hours, cool to 30°C, filter, wash the filter cake with toluene, distill under reduced pressure at 70°C, and then distill under vacuum at 80°C until no droplets flow out, to obtain an antioxidant; The flame retardant filler is prepared by the following steps: Step B1: In a nitrogen atmosphere, castor oil was added to a reaction bottle, refluxed and stirred, aminopropyl heptaisobutyl POSS and sodium methoxide were added, and refluxed and stirred at 100-110° C. for 24 h to obtain a hydroxyl product; Step B2: Add the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide into a flask to obtain a mixed solution 1; add 4-dimethylaminobenzoyl chloride into dimethyl sulfoxide to obtain a mixed solution 2; slowly dropwise add the mixed solution 2 into the mixed solution 1 in an ice-water bath at 0°C; after the dropwise addition is completed, heat to 40°C, stir and react at a constant temperature for 8-10 hours, and distill under reduced pressure to obtain a tertiary amine product; Step B3: Place the tertiary amine product and ethanol in a flask, start stirring, then add 1-chloropentane, heat to 50-60°C, stir and react at constant temperature for 10-12h, recrystallize with acetone after rotary evaporation, and filter to obtain a quaternary ammonium salt; add distilled water, ethanol, and quaternary ammonium salt to a three-necked flask, heat to 80°C with stirring, then add montmorillonite, continue stirring and reacting for 12-14h, then wash with ethanol, vacuum dry, and grind to obtain a flame retardant filler.

2. The aging-resistant overhead cable according to claim 1, characterized in that: In step A1, the usage ratio of capsaicin, toluene, sodium hydroxide solution and epichlorohydrin is 0.1 mol:85-95 mL:5-10 mL:0.1 mol, and the mass fraction of sodium hydroxide solution is 10%.

3. The aging-resistant overhead cable according to claim 1, characterized in that: In step A2, the usage ratio of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid, toluene, pyridine and epoxidation product is 0.1 mol:140-150 mL:0.010-0.015 mol:0.1 mol.

4. The aging-resistant overhead cable according to claim 1, characterized in that: In step A3, the usage ratio of the alcoholic hydroxyl product and toluene is 0.1 mol: 150-160 mL; the usage ratio of diethylphosphite chloride, triethylamine and toluene solution of the alcoholic hydroxyl product is 23.4-24.5 g: 20-25 mL: 155-165 mL.

5. The aging-resistant overhead cable according to claim 1, characterized in that: In step B1, the usage ratio of castor oil, aminopropyl heptaisobutyl POSS and sodium methoxide is 100-110 g: 60-65 g: 5-6 g.

6. The aging-resistant overhead cable according to claim 1, characterized in that: In step B2, the amount ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 140-150g: 0.01-0.015mol: 0.1mol: 260-270mL; the amount ratio of 4-dimethylaminobenzoyl chloride and dimethyl sulfoxide is 0.1mol: 40-50mL; the amount ratio of mixed solution 1 and mixed solution 2 is 265-275mL: 45-55mL.

7. The aging-resistant overhead cable according to claim 1, characterized in that: In step B3, the usage ratio of the tertiary amine product, ethanol, and 1-chloropentane is 155-165 g: 335-345 mL: 0.1 mol, and the volume fraction of ethanol is 95%; the usage ratio of distilled water, ethanol, quaternary ammonium salt, and montmorillonite is 60 mL: 60 mL: 163-173 g: 10 g.

8. The aging-resistant overhead cable according to claim 1, characterized in that: The wire core is formed by twisting a number of hard aluminum wires, and the insulating layer is made of fluororubber; the silane coupling agent is vinyl tris (2-methoxyethoxy) silane, the vulcanizing agent is diisopropylbenzene peroxide, and the crosslinking auxiliary agent is triallyl isocyanurate.

Citation Information

Patent Citations

  • Polyhedral oligomeric silsesquioxane (POSS)-containing alpha-amino triethoxy silane as well as preparation method and application thereof

    CN113248714A

  • High-flame-retardant insulated power cable and preparation method thereof

    CN118571552A

Cited By

  • Low-temperature-resistant overhead cable for power transmission line

    CN121812265A